Quality attributes for mobile applications - Fernandes, João M. (2016)
A mobile application is a type of software application developed to run on a mobile device. The chapter discusses the main characteristics of mobile devices, since they have a great impact on mobile applications. It also presents the classification of mobile applications according to two main types: native and web-based applications. Finally, this chapter identifies the most relevant types of quality attributes for mobile applications. It shows that the relevant quality attributes for mobile applications are usually framed in the Usability, Performance, and Maintainability and Support categories.